Outcome of Pregnancy in Women with Mitral Stenosis - Akhter, Nargis; Rahman, Fazlur; Salman, Mohammad; Anam, Khairul; Akther, Pervin; Naher, S Hamsun; Fatama, Nilufar; Hasan, Zahidul; Rashid, MA; Faruq, M; et al. (University Heart Journal, 2011)
The aim of this study was to evaluate the maternal and fetal outcome of pregnancy in mitral stenosis. This prospective study was carried out over period of 4 years (2005-2009) involving 50 pregnant patients with mitral stenosis. 30 (60%) had single valve involvement and mitral stenosis was the most predominant lesion (60%). 7 patients (14%) had undergone interventional and surgical correction prior to the onset of pregnancy. 12 (24%) patients presented at NYHA class III-IV. Women with MS had 10% pulmonary edema. 8 (16%) developed different types arrhythmia. There was one (1.67%) meternal death has been reported in this series. The incidence of preterm birth and small for gestational age newborn was 12% and 14% respectively. Pregnancy in women with valvular heart diseases associated with remarkable unfavourable effect on maternal and fetal outcome which are related to severity of disease. Keywords: Mitral stenosis; Pregnancy. DOI: 10.3329/uhj.v6i2.7248 University Heart Journal Vol. 6, No. 2, July 2010 pp.74-77